The Influence of Attractions, Facilities and Accessibility on Tourist Satisfaction at Parai Tenggiri Beach, Bangka Regency - Nopriana, Anisa; Valeriani, Devi; Kurniawan, Kurniawan; Sugeng, Novita Widyastuti (Institut Pariwisata Trisakti, 2024)
This research aims to determine the influence of attractions, facilities and accessibility on tourist satisfaction. This type of research is quantitative descriptive research with multiple analysis methods. The total population in this study was 23,112 people based on January 2021 to December 2021, while the sample used the Slovin formula to be 100 respondents. The research results show that facilities and accessibility have a significant effect on tourist satisfaction. The natural beauty of the beach, with white sand and granite rocks, as well as recreational activities such as fishing and diving, add to the visitor experience. Adequate facilities and good accessibility also increase tourist comfort and satisfaction, encouraging them to return. Managers are expected to improve natural attractions, introduce new activities, and improve the quality of facilities such as toilets and eating places. Accessibility must also be considered with the development of transportation infrastructure and clear information about locations. Keywords: attractions, accessibility facilities, tourist satisfaction